Raso, Laura (2017). Sin coartadas. Ética de la escritura de Liliana Heker durante el menemato. Córdoba: Portaculturas. 186 pp. - Cabrera, Mario Federico David (2018)
Fil: Cabrera, Mario Federico David. Universidad Nacional de San Juan